1995
DOI: 10.1037/0022-3514.68.1.116
|View full text |Cite
|
Sign up to set email alerts
|

Linguistic intergroup bias: Differential expectancies or in-group protection?

Abstract: The linguistic intergroup bias describes the tendency to communicate positive in-group and negative out-group behaviors more abstractly than negative in-group and positive out-group behaviors. This article investigated whether this bias is driven by differential expectancies or by in-group protective motives. In Exp 1, northern and southern Italian participants (N=151) described positive and negative behaviors of northern or southern protagonists that were either congruent or incongruent with stereotypic expec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
171
2
10

Year Published

1998
1998
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(201 citation statements)
references
References 19 publications
(47 reference statements)
18
171
2
10
Order By: Relevance
“…These predictions may be seen as analogous to those of the linguistic intergroup bias (e.g., Hamilton et al, 1992;Maass & Arcuri, 1992;Maass et al, 1995;Maass et al, 1989). However, whereas the linguistic intergroup bias is concerned with perceivers' outward descriptions of particular acts, the proposed judgment bias focuses on the extent to which particular acts are spontaneously considered during the group judgment process.…”
Section: Intergroup Bias In the Judgment Processmentioning
confidence: 72%
See 3 more Smart Citations
“…These predictions may be seen as analogous to those of the linguistic intergroup bias (e.g., Hamilton et al, 1992;Maass & Arcuri, 1992;Maass et al, 1995;Maass et al, 1989). However, whereas the linguistic intergroup bias is concerned with perceivers' outward descriptions of particular acts, the proposed judgment bias focuses on the extent to which particular acts are spontaneously considered during the group judgment process.…”
Section: Intergroup Bias In the Judgment Processmentioning
confidence: 72%
“…Second, perceivers require less evidence to accept an expected versus an unexpected conclusion (Trope & Liberman, 1996). Consistent with these biases, expected behaviors are more likely to yield dispositional inferences than unexpected behaviors (e.g., Bodenhausen & Wyer, 1985;Hastie, 1984;Maass et al, 1995). This research suggests that perceivers may place greater trust in evidence suggesting in-group superiority than inferiority, and may draw corresponding inferences more readily.…”
mentioning
confidence: 72%
See 2 more Smart Citations
“…More recently, subsequent research has shown that the LIB can be considered as a specific example of a more general phenomenon. That is, in general, expectancy consistent behaviors are described at a higher level of linguistic abstraction than expectancy inconsistent behaviors (Maass, 1999;Maass, Milesi, Zabbini, & Stahlberg, 1995;Wigboldus et al, 2000). This more general linguistic phenomenon has been labeled the linguistic expectancy bias or LEB (Maass, 1999;Wigboldus et al, 2000).…”
Section: Biased Language Usementioning
confidence: 99%